2011
DOI: 10.1038/ni.2137
|View full text |Cite
|
Sign up to set email alerts
|

The IκB kinase complex regulates the stability of cytokine-encoding mRNA induced by TLR–IL-1R by controlling degradation of regnase-1

Abstract: Toll-like receptor (TLR) signaling activates the inhibitor of transcription factor NF-κB (IκB) kinase (IKK) complex, which governs NF-κB-mediated transcription during inflammation. The RNase regnase-1 serves a critical role in preventing autoimmunity by controlling the stability of mRNAs that encode cytokines. Here we show that the IKK complex controlled the stability of mRNA for interleukin 6 (IL-6) by phosphorylating regnase-1 in response to stimulation via the IL-1 receptor (IL-1R) or TLR. Phosphorylated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
307
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 257 publications
(328 citation statements)
references
References 40 publications
19
307
2
Order By: Relevance
“…It has been recently shown that levels of Regnase-1 expression are regulated through TLR signaling, in which Regnase-1 is induced in peritoneal macrophages after LPS treatment (8,9). Interestingly, levels of Arid5a protein were also controlled through TLR signaling.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It has been recently shown that levels of Regnase-1 expression are regulated through TLR signaling, in which Regnase-1 is induced in peritoneal macrophages after LPS treatment (8,9). Interestingly, levels of Arid5a protein were also controlled through TLR signaling.…”
Section: Discussionmentioning
confidence: 92%
“…For example, TTP phosphorylation by MK2 downstream of p38 MAPK signaling facilitates TTP to degrade mRNA through inhibition of deadenylase (28). Regnase-1 is phosphorylated by the IκB kinase (IKK) complex downstream of myeloid differentiation primary response protein 88 (Myd88) signaling, which undergoes ubiquitination and degradation (8). Accordingly, it is possible that the binding activity of Arid5a is also regulated by specific protein kinases, including p38 MAPK and IKK complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group and the Akira group clarified the post-transcriptional regulatory mechanisms of IL-6 mRNA by two counteractive molecules [11,12]. Akira et al found that Regnase-1, a kind of nuclease, which binds at the site 3'-untranslated region (3'-UTR) and destabilizes of IL-6 mRNA.…”
mentioning
confidence: 99%